Childhood sexual abuse and substance abuse: A gender paradox?. (January 2017) - Tonmyr, Lil; Shields, Margot
Abstract: We examine associations between childhood sexual abuse (CSA) and substance abuse, the role of mental health indicators as mediators in these associations and whether or not associations differ by gender. Data are from 14, 063 respondents aged 18–76 years from the 2004–2005 Canadian Gender, Alcohol, and Culture: An International Study (GENACIS). Multiple logistic regression models were used to examine associations between CSA and substance abuse variables, controlling for socio-demographic factors. Odds were adjusted by indicators of mental health to assess if these variables mediated associations between CSA and substance abuse. Tests of interactions between sex and CSA were conducted to see if gender differences exist in associations. In 2004/2005, CSA was reported by 14% of women and 5% of men. CSA was associated with heavy drinking, hazardous drinking, and the use of marijuana, other illicit drugs, and off-label drugs. Associations were only very marginally attenuated when controlling for depression and self-perceived emotional/mental health. In all cases previously observed significant associations persisted. Evidence of gender differences in associations between CSA and substance abuse was negligible. Preventing CSA may also reduce substance abuse.